2019
DOI: 10.1002/jcb.29552
|View full text |Cite
|
Sign up to set email alerts
|

Role of miR‐106‐mediated mitogen‐activated protein kinase signaling pathway in oxidative stress injury and inflammatory infiltration in the liver of the mouse with gestational hypertension

Abstract: We aim to investigate the role of miR‐106‐mediated mitogen‐activated protein kinase (MAPK) signaling pathway in oxidative stress (OS) injury and inflammatory infiltration in the liver of the mouse with gestational hypertension (GH). Ninety specific pathogen‐free mice (Kunming species) during middle to late gestation were selected for the study. Fifteen mice were used as control, while the rest were used for establishing the GH model. The mice were assigned to six groups: normal group (normal gestation), model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Similarly, increased levels of reactive oxygen species (ROS) resulted to the decreased expression of miR-106a ( Wang et al, 2010 ). On the other hand, elevated levels of miR-106a prevented oxidative stress injury and inflammation in hepatic mouse with gestational hypertension ( Wang Z. et al, 2019 ), resulting to repression of the expressions of HIF1-α and VEGF in diabetic retina ( Ling et al, 2013 ). In addition, miR-106a has been associated with macrophage activation, suggesting its involvement in inflammation ( Zhu et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, increased levels of reactive oxygen species (ROS) resulted to the decreased expression of miR-106a ( Wang et al, 2010 ). On the other hand, elevated levels of miR-106a prevented oxidative stress injury and inflammation in hepatic mouse with gestational hypertension ( Wang Z. et al, 2019 ), resulting to repression of the expressions of HIF1-α and VEGF in diabetic retina ( Ling et al, 2013 ). In addition, miR-106a has been associated with macrophage activation, suggesting its involvement in inflammation ( Zhu et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Studies have found that miR-106a inhibited oxidative stress injury and inflammatory infiltration in the liver of the mouse with gestational hypertension by inhibiting the mitogen-activated protein kinase signaling pathway. 31 MiR-106b expression was significantly inhibited in activated bone marrow derived dendritic cells (BMDCs) stimulated by OVA. And miR-106b negatively regulated the allergic properties of BMDCs and subsequent Th2 polarization by targeting early growth response (Egr)-2.…”
Section: Discussionmentioning
confidence: 99%
“…Other miRNAs differentiating the SWR/J control from the WT control group of mice, such as miR-20 and miR-106, are associated with the regulation of glucose metabolism [33], whilst miR-93 and miR-106 might affect liver diseases [34]. Additionally, miR-106 has been linked with regulation of the MAPK signaling pathway during oxidative stress [35]. The differences in expression of these miRNAs in the serum of NET-KO, SWR/J and WT mice under control conditions may affect the subsequent genotype dependent stress response.…”
Section: Discussionmentioning
confidence: 99%